Efektivitas Penggunaan Teknologi Digital dalam Mengurangi Tingkat Kecemasan Ibu Hamil: A Systematic Literature Review (Journal Genta Kebidanan, 2025)
Anxiety during pregnancy is a significant mental health issue and can adversely affect the well-being of the mother as well as the development of the fetus. In recent years, digital technology has emerged as an alternative intervention with the potential to reduce prenatal anxiety. This article is a Systematic Literature Review (SLR) aimed at assessing the effectiveness of using digital technology in reducing anxiety levels in pregnant women. This research was conducted in accordance with PRISMA guidelines and includes literature from the PubMed, ScienceDirect, IEEE Xplore, and Google Scholar databases published in the last decade. The research shows that various forms of digital technology, such as app-based mindfulness interventions (eMBI), internet-based cognitive behavioral therapy (iCBT), tele-education, and online peer support platforms, are significantly effective in reducing prenatal anxiety. The analyzed research applied quantitative and qualitative methods with validated psychometric instruments, such as STAI, PRAQ-R, GAD-7, and EPDS. Although the results are promising, further research is needed with a randomized controlled trial (RCT) design, larger sample sizes, and the development of specific measurement instruments for perinatal anxiety. The practical implications of this research indicate that healthcare professionals can integrate digital technology into prenatal services to efficiently enhance psychological support, especially in resource-limited areas
Keywords: Anxiety; Digital Technology; Health Applications; iCBT; Telemedicine